Definitive three-dimensional high-dose-rate brachytherapy for inoperable endometrial cancer - Draghini, Lorena; Maranzano, Ernesto; Casale, Michelina; Trippa, Fabio; Anselmo, Paola; Arcidiacono, Fabio; Fabiani, Stefania; Italiani, Marco; Chirico, Luigia; Muti, Marco (Journal of Contemporary Brachytherapy, 2017)
Purpose : To report our experience on high-dose-rate brachytherapy (HDR-BT) in patients with stage I-III endometrial cancer unfit to surgery. Material and methods : Seventeen patients underwent HDR-BT as definitive treatment. Median age was 79 years (range, 60-95), median Karnofsky performance status 90% (range, 60-100). Histology was endometrial adenocarcinoma in 14 (82%), and non-endometrial in 3 (18%) patients. In 15 (88%) patients, clinical stage was I and in remaining 2 (12%) was III. All patients were evaluated with computed tomography (CT) and endometrial biopsy. Using the Fletcher applicator, a CT-based planning HDR-BT was delivered. Local control (LC) was obtained when there was an interruption of vaginal bleeding in absence of CT-imaging progression. Results : Fourteen patients underwent HDR-BT alone and three external beam radiotherapy (EBRT) combined with HDR-BT. All patients had a clinical LC, after a median follow-up of 53 months (range, 6-131), 3 and 6 years LC rates were 86% and 69%, respectively. Cancer specific survival (CSS) at 1, 2, and 6 years was 93%, 85%, and 85%, respectively. Age, stage, dose, and type of radiotherapy did not result significant prognostic factors for LC and CSS. Only histology significantly influenced LC: for high-risk histology (i.e., non-endometrial carcinoma or grade [G] 3 endometrial adenocarcinoma) LC was 73% at 1 year and 36% at 6 years; for low-risk histology (i.e., G1-2 endometrial adenocarcinoma) was 100% at 1 and 6 years (p = 0.05). Two (12%) patients had G2 acute toxicity and two others (12%) G1 late toxicity. Conclusions : Although some limitations of our analysis (relatively few number of patients recruited, retrospective evaluation, and consequent suboptimal patient selection), it confirms effectiveness and safety of definitive HDR-BT for medically inoperable stage I-III endometrial cancer. The best LC was obtained in stage I low-risk histology.